Pengembangan Produksi UMKM Aneka Keripik Di Desa Mekargalih Kec.Jatiluhur Purwakarta Melalui Pelatihan Branding - Madien Azizah, Firdha; Pahrudin, Sahrul (STIE Syariah Indonesia Purwakarta, 2023)
There are several problems related to MSME with various chips, one of which is the limited technological knowledge of MSME actors in marketing various chips products, and they have not done marketing digitally (online) so they cannot compete with other MSME who have used digital marketing first. This PKM program aims to make MSME, especially MSME with various chips, have attractive product brands and product previews, as well as be a differentiator with products from other MSME. The community service program regarding the Development of MSME Production of Various Chips in Mekargalih Village, Jatiluhur District, Purwakarta Through Branding Training is felt by the community, especially MSME of various chips. raw material for the production of various other chips. Furthermore, this assistance gives a new color to the packaging of various chips for MSME. In addition to economic-based PKM, other supporting activities such as cement alms for ta'lim majlis and donations for orphans, are deeply felt by the community, especially the recipients of compensation from orphans. Hopefully, the sacrifice of the PKM team can be useful for the wider community, especially the community in the Mekargalih village, Jatiluhur sub-district, Purwakarta district, and can be a good charity savings in the hereafter.